Strategi Komunikasi PT Airmas Perkasa dalam Meningkatkan Hubungan dengan External Stakeholder di Masa Pandemi - Aisyahna Aulia; Stevani (Jurnal Spektrum Komunikasi, 2022)
The COVID-19 pandemic, which has spread throughout the world, poses a challenge for business people in implementing a communication strategy to reach out to their stakeholders. In addition to maintaining and enhancing the company's good name in public, a communication strategy is also useful for improving relationships with company stakeholders, both internal and external stakeholders. This research was conducted using descriptive qualitative research methods, based on the interactional communication strategy by Wilbur Schramm. The results of the research findings show that the implementation of the communication strategy carried out by PT Air Mas Perkasa uses the communication media Instagram, Youtube, Zoom, and interpersonal communication in improving relationships with stakeholders, especially external stakeholders during the COVID-19 pandemic. The feedback obtained after using social media as a company communication medium is public awareness about PT Air Mas Perkasa.